2023
DOI: 10.3390/jcm12030898
|View full text |Cite
|
Sign up to set email alerts
|

Suprapapillary Biliary Stents Have Longer Patency Times than Transpapillary Stents—A Systematic Review and Meta-Analysis

Abstract: Background and study aims: Endoscopic biliary stent placement is a minimally invasive intervention for patients with biliary strictures. Stent patency and function time are crucial factors. Suprapapillary versus transpapillary stent positioning may contribute to stent function time, so a meta-analysis was performed in this comparison. Methods: A comprehensive literature search was conducted in the CENTRAL, Embase, and MEDLINE databases to find data on suprapapillary stent placement compared to the transpapilla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 45 publications
(225 reference statements)
0
5
0
Order By: Relevance
“…The major concern with uncovered stents remains the risk for obstruction by tumor ingrowth, resulting in recurrent cholangitis. For this reason, some groups have opted for new therapy modalities using plastic or intraductal papillary stents [32,33]. RFA has great potential in this regard, with results that demonstrated improved stent patency and improved patient survival.…”
Section: Rfa+s S-alonementioning
confidence: 99%
“…The major concern with uncovered stents remains the risk for obstruction by tumor ingrowth, resulting in recurrent cholangitis. For this reason, some groups have opted for new therapy modalities using plastic or intraductal papillary stents [32,33]. RFA has great potential in this regard, with results that demonstrated improved stent patency and improved patient survival.…”
Section: Rfa+s S-alonementioning
confidence: 99%
“…23 Since the distal end of the PS is located in the CBD for IS placement, IS placement can reduce the risk of intestinal juice reflux and food impaction and has been reported to have long-term stent patency. [24][25][26][27] Kuwatani et al reported the possibility of bacteria entering the CBD via a PS thread. 28 In our study, PS without threads or nylon was used in only two cases in the unilateral group.…”
Section: Discussionmentioning
confidence: 99%
“…Stent sludge occlusion is one of the major reasons for RBO in PS and is related to bacterial biofilm formation due to intestinal juice reflux and food impaction 23 . Since the distal end of the PS is located in the CBD for IS placement, IS placement can reduce the risk of intestinal juice reflux and food impaction and has been reported to have long‐term stent patency 24–27 . Kuwatani et al.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the anatomical variation of the patients, their overall comorbidities, previous antitumor therapy, or any other number of factors could be influencing the rate of duodenal invasion. 4 Without ruling out these confounding factors, we cannot conclusively say that it is the proximity to the AOV alone that is causing the higher rates of invasion.…”
mentioning
confidence: 98%
“…The study seems to imply that the shortened stent patency in cases closer to the AOV is due to increased food retention and consequent reflux. 4,5 While this is a plausible theory, it remains just that-a theory-unless directly tested. At first glance, this explanation seems logical.…”
mentioning
confidence: 99%